Analisis Model Pembelajaran Project Based Learning Terhadap Penguatan Karakter Siswa Kelas IV di MI Quba Kota Sorong - Munira, Munira (Al-Khidmah : Jurnal Pengabdian dan Pendampingan Masyarakat, 2025)
This research aims to describe how the Project Based Learning (PJBL) learning model is implemented to strengthen the character of the Pancasila student profile of class IV students collection tencningques using interviews, observation and documentation. The population in this study were students in class IVA MI Quba, Sorong City, totaling 21 students. The research results obtained show that the application of the Project Based Learning model can strengthen the character profil of Pancasila students in creating project where studentare more creative in creating their own works by managing waste and turning it into unique items. Based on the result of observations, each student has an average creative level that is able to create something unique that can be reused. This proves that the Project Based Learning model can help students strengthen their character by creating a project that can be used or reused